INFLUENCE OF TEACHING SKILLS, TEACHER WELFARE, TEACHER PERSONALITY COMPETENCE, AND TEACHING MOTIVATION ON THE INTENTION TO BECOME A TEACHER FOR ECONOMICS EDUCATION STUDENTS AT JAKARTA STATE UNIVERSITY - Nurkristianingrum, Nida; Nurjanah, Siti; Wibowo, Agus (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
The problem in this study is the lack of graduates of students majoring in economic education who become teachers. This study aims to determine the effect of teaching skills, teacher welfare, teacher personality competence, and teaching motivation on interest in becoming a teacher in economic education students at the State University of Jakarta. This study uses the Path Analysis method. The population in this study was 88 students majoring in Economic Education who had practiced teaching skills in schools. The data collection technique was a questionnaire that was distributed via Google Forms. The questionnaire is valid and reliable based on the test results obtained. Then, the data collected from the agent results were analyzed using multiple linear regression. From the analysis, it was found that the Teaching Skills variable (X1) had a positive but insignificant effect on Teaching Motivation (X4) with a value of 0.473> 0.05. At the same time, the Teacher Welfare variable (X2) has a positive and significant effect on Teaching Motivation (X4) with a value of 0.030 < 0.05. The Teacher Personality Competence variable (X3) also has a positive and significant impact on Teaching Motivation (X4) with a value of 0.001 < 0.05. The Teaching Skills variable (X1) has a positive and significant effect on the Intention to Become a Teacher (Y) with a value of 0.001 < 0.05. Teacher Welfare (X2) has a positive and significant effect on Intention to Become a Teacher (Y) with a value of 0.001 <0.05. Teaching Motivation (X4) has a positive and significant effect on Intention to Become a Teacher (Y) with a value of 0.005 <0.05. From the results of the F test, a significance value of 0.001 is obtained, meaning that the value of 0.001 <0.05, it can be concluded that the variable PKM (X1), Teacher Welfare (X2), the variable Use of Teacher Personality (X3) and Teaching Motivation (X4) simultaneously affects the variable Interest in Becoming a Teacher (Y).